Menangkal Genosida Agama dengan Pendidikan Islam Berbasis Multikultural - Amru Almutasim (STAIFAS-Press, 2016)
Diversity has become a part of history and the reality of human life, so he was a natural phenomenon whose existence can not be denied. But in concrete reality, diversity has made man trapped in a destructive attitudes. The existence of conflicts between different communities with a background of SARA (Tribe, Religion, Race and intergroup). Of the many triggers, the factors of religious differences, even differences in religious ideology, is a factor that can not be excluded. Cases of violence and war in various parts of the world, shows how religion has been used as a means of